Regulation of Free Fatty Acid Receptor 4 on Inflammatory Gene Induced by LPS in Large Yellow Croaker (Larimichthys crocea) - Wu, Mengjiao; Li, Qingfei; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2021)
Free fatty acid receptor 4 (FFAR4) plays a key role in regulating the inflammatory response in mammals. The present study aimed to investigate the function of large yellow croaker FFAR4 on inﬂammation. In the present study, ffar4 was expressed in 10 tissues of large yellow croaker with the higher expression in gill, brain, eye, muscle and head kidney. Further studies showed that treatment of macrophages with agonists (TUG891 or GSK137647A) or overexpression of ffar4 reduced the mRNA expression of pro-inflammatory genes induced by LPS, and increased the expression of pparγ. Treatment of macrophages with antagonist AH7614 increased the mRNA expression of pro-inflammatory genes induced by LPS, and decreased the mRNA expression of pparγ. In order to verify the immunomodulatory effect of PPARγ, pparγ was overexpressed in macrophage which significantly reduced the mRNA expression of pro-inflammatory genes il6, il1β, il8, tnfα and cox2. Moreover, results of dual-luciferase assays showed that PPARγ downregulated the transcriptional activity of il6 and il1β promoters. In conclusion, FFAR4 showed anti-inflammatory effects on LPS-induced inflammation in large yellow croaker.